Bounded rationality: from fast and frugal heuristics to logic programming and back - Francisco Vargas; Laura Martignon; Keith Stenning (Mind & Society, 2023)
The notion of "bounded rationality" was introduced by Simon as an appropriate framework for explaining how agents reason and make decisions in accordance with their computational limitations and the characteristics of the environments in which they exist (seen metaphorically as two complementary scissor blades).We elaborate on how bounded rationality is usually conceived in psychology and on its relationship with logic. We focus on the relationship between heuristics and some non-monotonic logical systems. These two categories of cognitive tools share fundamental features. As a step further, we show that in some cases heuristics themselves can be formalized from this logic perspective. We have therefore two main aims: on the one hand, to demonstrate the relationship between the bounded rationality programme and logic, understood in a broad sense; on the other hand, to provide logical tools of analysis of already known heuristics. This may lead to results such as the characterization of fast and frugal binary trees in terms of their~associated logic program here provided.
Keywords: 300; Non-monotonic reasoning; Bounded rationality; Ecological rationality; Logic programming; Heuristics